2018
DOI: 10.1521/aeap.2018.30.5.369
|View full text |Cite
|
Sign up to set email alerts
|

“I Don't Need PrEP Right Now”: A Qualitative Exploration of the Barriers to PrEP Care Engagement Through the Application of the Health Belief Model

Abstract: The Health Belief Model has been useful for studying uptake of HIV prevention behaviors and has had limited application to understanding utilization of pre-exposure prophylaxis (PrEP), a biomedical strategy to reduce HIV acquisition. We recruited 90 persons undergoing HIV screening and educated them about PrEP. We followed up with 35 participants approximately 3 weeks later and quantitatively assessed PrEP uptake. No participant had initiated PrEP. We conducted in-depth interviews with 15 participants to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 21 publications
0
23
0
2
Order By: Relevance
“…At the individual level, there are simple logistical constraints to accessing PrEP, exacerbated by socioeconomic inequalities. For example, individuals may experience difficulty in getting to the clinic [74] due to lack of transportation [46] or time constraints [75,76]. A 2016 National Survey on HIV in the Black community found that 38% of 787 participants were more than one hour's drive from a PrEP provider.…”
Section: Lack Of Access To Medical Care As a Barrier To Prep Uptakementioning
confidence: 99%
“…At the individual level, there are simple logistical constraints to accessing PrEP, exacerbated by socioeconomic inequalities. For example, individuals may experience difficulty in getting to the clinic [74] due to lack of transportation [46] or time constraints [75,76]. A 2016 National Survey on HIV in the Black community found that 38% of 787 participants were more than one hour's drive from a PrEP provider.…”
Section: Lack Of Access To Medical Care As a Barrier To Prep Uptakementioning
confidence: 99%
“…74,92,93,97 PWID attending SSPs report greater awareness of PrEP, suggesting that SSPs provide an effective avenue for increasing PrEP awareness and utilization. [83][84][85]98 Several studies have found that PWID prefer accessing PrEP at SSPs where there may be less stigma and greater comfort, and colocation could reduce the burden of additional clinical visits. [83][84][85][86]89 Providers also prefer service colocation, which could include placing PrEP providers within an SSP or allowing standing PrEP orders for PWID at SSPs.…”
Section: Role Of Syringe Services Programs In Hiv Testingmentioning
confidence: 99%
“…Our study was guided by the Health Belief Model (HBM) [36,37]. This framework understands that a behavior (e.g., using PrEP) is affected by several interacting factors including the perceptions of threat and benefit, cues to action, and the person's own sense of capacity to perform the behavior.…”
Section: Theoretical Frameworkmentioning
confidence: 99%